2014
DOI: 10.1902/jop.2013.130043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implant Diameter on Its Survival: A Meta‐Analysis Based on Prospective Clinical Trials

Abstract: This meta-analysis showed that narrower implants (<3.3 mm) had significantly lower survival rates compared with wider implants (≥3.3 mm). Other variables, such as type of prosthesis, implant surface, and timing of prosthetic loading, were found to have influenced the implant survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 46 publications
4
71
3
5
Order By: Relevance
“…The between‐group difference was statistically significant ( P = 0.001). When comparing prosthetic outcomes reported in the literature with regard to the complications reported in this study, trends appear similar 1 , 4 . Decementation and screw loosening were the most frequent complications in the NDI group, occurring at 8.2% and 6.1%, respectively.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The between‐group difference was statistically significant ( P = 0.001). When comparing prosthetic outcomes reported in the literature with regard to the complications reported in this study, trends appear similar 1 , 4 . Decementation and screw loosening were the most frequent complications in the NDI group, occurring at 8.2% and 6.1%, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Romeo et al 28 reported survival rates of 92% to 97.7% for NDIs and SDIs supporting both single restorations and FPDs in anterior and posterior areas over a 7‐year observation period. However, a recent meta‐analysis by Ortega‐Oller et al 1 showed NDIs could be at higher risk for implant failure. In particular, it was found that NDIs with a diameter <3.3 mm had failure rates 3.92 times greater than implants with a diameter ≥3.3 mm after an average follow‐up time of 4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants with narrow diametes of 3.0 to 3.25 mm are well documented only for single-tooth, non-load-bearing regions [25]. A meta-analysis study showed that narrower implants had significantly lower survival rates compared with wider implants [26]. Moreover, most authors advice at least 1 mm residual bone present to the adjacent to the implant surface [25].…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9] Substantial evidence indicates that treatment with mandibular CD is often unsuccessful, and thus, the implant-retained mandibular overdentures (MOs) should be the minimum treatment offered to edentulous patients. 13,14 Different options have been proposed to overcome these limitations, such as narrow diameter implants (NDI). 12 These clinical limitations, together with the continuous resorption of the alveolar ridge and significant decrease in bone volume, mainly in the horizontal sense, may limit the utility of standard diameter implants in this population in the absence of additional surgical techniques for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%